Newly Diagnosed Bipolar Disorder and the Subsequent Risk of Erectile Dysfunction: A Nationwide Cohort Study. Issue 2 (1st February 2018) - Hou, Po-Hsun; Mao, Frank Chiahung; Chang, Geng-Ruei; Huang, Min-Wei; Wang, Yao-Ting; Huang, Shiau-Shian
Abstract: Background: Although erectile dysfunction (ED) is a common problem in men with mental disorders, there are few reports in the literature on the relation between bipolar disorder (BD) and ED. Aims: To establish the incidence rate of ED in men with BD and assess the risk of ED in patients with BD according to type of treatment offered or no active treatment with medication during the 1st year of onset. Methods: We identified 5, 150 men with newly diagnosed BD using Taiwan's National Health Insurance Research Database. 2 matched controls per case were selected using the propensity score and a greedy matching method to obtain a balanced control group. Multivariate Cox regression analysis was used to examine the independent risk factors for ED, including obesity and comorbidities. Hazard ratios (HRs) for ED risk were calculated for the different psychotropic therapy groups, including antidepressants, antipsychotics, and mood stabilizers. Outcome: HRs for ED risk were calculated for the different psychotropic therapy groups, including antidepressants, antipsychotics, and mood stabilizers. Patients with BD had a significantly higher HR for an ED diagnosis than controls. Results: Patients with BD had a higher HR for an ED diagnosis than controls. Although some psychotropic medications can increase the risk of ED, patients with BD not actively treated with medication still showed a higher risk of ED than controls. Clinical Implications: Because ED might be more prevalent in patients with BD than in the general population, clinicians should assess erectile function when selecting appropriate treatment for patients with BD to minimize the risk of ED as an annoying side effect and improve treatment compliance. Strengths and Limitations: This is the first large-scale population-based study to explore the association between BD and ED. A particular strength of this study is its nationwide, population-based study design, which afforded substantial statistical power for detecting subtle differences between the 2 cohorts, thereby minimizing selection bias. There are some limitations to the present study. (i) Data on other potential risk factors is lacking. (ii) Patient compliance and dose effect between psychotropic medication and ED could not be established. (iii) We could not assess the relation between ED and the severity and phases of BD. Conclusion: This cohort study found a temporal association between BD and subsequent ED in a large national sample of men. Clinicians should consider the risk of ED when choosing treatment for patients with BD.